2010
DOI: 10.1097/brs.0b013e3181cf39ff
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Based Screening Test for Idiopathic Scoliosis Using Cellular Dielectric Spectroscopy

Abstract: This cell-based assay can serve as a presymptomatic screening test to identify asymptomatic children at risk of developing IS and may be used to improve stratification of patients, which in turn allow clinicians to predict their clinical outcome. Moreover, this functional blood test is advantageous because it can be performed without prior knowledge of specifically mutated genes causing IS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 23 publications
2
31
0
1
Order By: Relevance
“…As expected, all patients were less responsive than control subjects, and patients classified in the same functional group by our new procedure exhibited similar levels of the maximum response ( Figure 5). Moreover, disparity between patients of each functional group was consistent with our classical range of classification 12 , validating our new procedure. The classification of a large cohort of scoliotic patients regularly followed in our special clinic at Sainte-Justine Hospital has revealed that the three functional groups were similarly distributed among moderate cases, while the FG2 was predominant among severe cases (Figure 6), identifying patients categorized into this functional group as more at risk for severe progression of the disease and indicating that this classification test can be useful in the prognosis of idiopathic scoliosis.…”
Section: Protocolsupporting
confidence: 84%
See 2 more Smart Citations
“…As expected, all patients were less responsive than control subjects, and patients classified in the same functional group by our new procedure exhibited similar levels of the maximum response ( Figure 5). Moreover, disparity between patients of each functional group was consistent with our classical range of classification 12 , validating our new procedure. The classification of a large cohort of scoliotic patients regularly followed in our special clinic at Sainte-Justine Hospital has revealed that the three functional groups were similarly distributed among moderate cases, while the FG2 was predominant among severe cases (Figure 6), identifying patients categorized into this functional group as more at risk for severe progression of the disease and indicating that this classification test can be useful in the prognosis of idiopathic scoliosis.…”
Section: Protocolsupporting
confidence: 84%
“…Using this procedure, asymptomatic and scoliotic children can be easily classified to better predict their clinical outcome without any danger for their health. However, when performing classification according to the degree of maximum response to Gi stimulation relative to the healthy control subjects 12 , several requirements for the control subjects should be met. Indeed, in order to have a proper comparison cohort, the control subjects must be age and gender matched, not be on any kind of medication, and provide private information, such as past individual/familial medical history.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these receptors mediate the transmission of intracellular signals by activating guanine nucleotide-binding proteins (G proteins) to which the receptor is coupled. Such receptors are generically referred to as G protein-coupled receptors ("GPCR"s) [30]. Ghrelin secretion is stimulated by several Gs-coupled receptors and inhibited by many Gicoupled and Gq receptors [31].…”
Section: Discussionmentioning
confidence: 99%
“…Such techniques have been applied to patients with AIS but, unfortunately, the picture that has emerged does not seem to be a simple one. Genetic research into AIS has shown many genes possibly to be involved and the picture is most certainly complex even though diagnostic tests are currently being developed (Akoume et al, 2010;Leboeuf et al, 2009;Ogilvie, 2010;Weinstein et al, 2008). This complexity might well reflect the complex nature of AIS (as described above) and the mixed nature of patients with possibly very different underlying causes.…”
Section: The Promise Of Genetic Studiesmentioning
confidence: 99%